THE RELATIONSHIP OF BODY MASS INDEX AND LENGTH OF SURGERY WITH INCIDENT SHIVERING ON PATIENT SPINAL ANESTHESIA - Pertami, Sumirah Budi; CT, Maria Diah; Ernawati, Naya; Y, Tri Johan Agus (Indonesian Journal of Applied Health, 2024)
Spinal anesthesia is a type of anesthesia that is injected into the cerebrospinal tract fluid (CSF) when a patient is undergoing surgery. Spinal anesthesia causes hypothermia which triggers shivering. Shivering is the body’s attempt to increase heat production and increase body temperature . Objective : To determine the relationship between body mass index and duration of surgery with the incidence of shivering in spinal anesthesia patients. Method: Correlation research with a cross sectional approach. The research sample composed of 73 respondents using accidental sampling data collection techniques. This research uses the Chi-Square test, point biserial test and logistic regression test as statistical analysis tests.Results : Statistical test results showed that there was a significant relationship between body mass index and the incidence of post anesthesia shivering. Conclusion: There is a relationship between body mass index and the incidence of post anesthesia. Keywords : Post Spinal Anesthesia Patients, Shivering Factor, Post Anesthesia Shivering